2017
DOI: 10.3390/ijms18112407
|View full text |Cite
|
Sign up to set email alerts
|

Lp16-PSP, a Member of YjgF/YER057c/UK114 Protein Family Induces Apoptosis and p21WAF1/CIP1 Mediated G1 Cell Cycle Arrest in Human Acute Promyelocytic Leukemia (APL) HL-60 Cells

Abstract: Lp16-PSP (Latcripin 16-Perchloric acid Soluble Protein) from Lentinula edodes strain C91-3 has been reported previously in our laboratory to have selective cytotoxic activity against a panel of human cell lines. Herein, we have used several parameters in order to characterize the Lp16-PSP-induced cell death using human acute promyeloid leukemia (HL-60) as a model cancer. The results of phase contrast microscopy, nuclear examination, DNA fragmentation detection and flow cytometry revealed that high doses of Lp1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Anticancer role of LP13 was revealed by cell cycle arrest at G 1 phase and apoptosis by NF-κB Signaling pathway in A549 cell line [ 17 ]. Lp16-PSP inhibited anchorage-independent growth; p21 WAF1/CIP1 mediated cell cycle arrest at the G 1 phase and apoptosis by the inhibition of NF-κB in leukemia cell line HL-60 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer role of LP13 was revealed by cell cycle arrest at G 1 phase and apoptosis by NF-κB Signaling pathway in A549 cell line [ 17 ]. Lp16-PSP inhibited anchorage-independent growth; p21 WAF1/CIP1 mediated cell cycle arrest at the G 1 phase and apoptosis by the inhibition of NF-κB in leukemia cell line HL-60 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…7A). Similarly, other studies reported that LP16-PSP, Asparagus officialis, and Cordycepin treated cancerous cells i.e., HL-60, human endometrial carcinoma ishikawa cells and leukaemia cells showed changes in mRNA expression of cell cycle related genes (Joseph et al, 2017;Liang et al, 2022;Shi et al, 2022). Scientific reports represented that cell cycle dysregulation cause's inhibition of cell growth or apoptosis and being considered as a marker for chemotherapeutic and chemo preventive agents (Zakaria et al, 2009).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 83%
“…6B). Previous studies also reported that mRNA expression level of Bax, capase-3, 8, 9, cytochrome-C, and PARP increases while Bcl-2 mRNA expression level was decreased which led the human leukemic cancer, breast cancer and Jurkat T-cell, cervical adenocarcinoma and hepatocellular carcinoma to apoptosis (Joseph et al, 2017;Kiddane et al, 2022;Mbazima et al, 2008;Sun et al, 2018;Zhu et al, 2015). Bcl-2 plays a vital role in apoptosis through maintaining mitochondria in active state.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…LP-7A was also reported possessing antiproliferative characteristics against breast cancer cells (Din et al, 2020). LP-11 and Lp16-PSP was reported as effective against human acute Promyelocytic Leukaemia HL-60 (Gao et al, 2018;Joseph et al, 2017). IC 50 was evaluated for anti-cancer effect of LP-5 protein on various human cancerous and normal cells line which includes (HepG2, A549, H1299, BGC-231, SGC-7901, MDA-MB-231 and MCF-7), and normal cells (HaCat).…”
Section: Discussionmentioning
confidence: 99%